Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan, Dan Dewan Komisaris Independen Terhadap Tax Avoidance - Adelia, Nova; Suhono, Suhono (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to analyze the influence of the variables profitability, leverage, company size, and independent board of commissioners on tax avoidance in manufacturing companies in the metal and similar subsector listed on the IDX for the period 2019-2023. The method used is quantitative, with data analysis employing classical assumption tests, descriptive analysis, and hypothesis testing. The population in this study consists of companies in the metal subsector and similar sectors listed on the IDX for the period 2019-2023. The sampling technique used in this study is purposive sampling, so the sample used in this study consists of 14 companies in the metal subsector and similar industries. Based on the research results, it was found that profitability partially has a positive and significant effect on tax avoidance, while leverage, company size, and independent board of commissioners partially do not have an effect on tax avoidance.